RETRACTED ARTICLE: THE USE OF SCIENCE ENVIRONMENT TECHNOLOGY AND SOCIETY (SETS) LEARNING MODEL FOR ENHANCING THE CRITICAL THINKING SKILLS AND SCIENTIFIC ATTITUDES - Maimunah, Maimunah (Jurnal Penelitian dan Pembelajaran IPA, 2017)
Abstract  This research purposed to determine the improvement of student’s scientific attitudes and critical thinking skills on the colloidal concept with implementation the learning model science environment technology and society (SETS). The method for this study is quasi-experimental with research design "Pretest-Posttest Nonequivalent Control Group Design". Class XI student at one of SMAN in Majalengka District is the sample in this research with 62 students. The written test and the observation sheets used for collecting the data. The results showed that SETS learning for colloidal concept can enhance the student’s scientific attitude was 72,7 % (good category) and student’s critical thinking skills with N-Gain of 42% (moderate category). Increasing student’s critical thinking skills class experiment is also significantly differ from the control class. So, the students’ scientific attitudes  and critical thinking skills can improved by implementation the learning chemistry with SETS learning model Keywords: Colloidal Systems, Critical Thinking Skills, Science Environment Technology and Society (SETS), Scientific Attitude